Green manufacturing: effect of vortex tube on machinability of Mild steel - Phoon, Sin Ye (2013)
This research presents a study on the effect of chilled air application through Vortex Tube during dry machining on the machinability of mild steel. Through the full factorial design of experiment, there is a total of 36 experiments had been conducted for two levels of spindle speed (100rpm and 215 rpm), three levels of depth of cut (1mm, 2mm and 3mm) and three levels of freed rate (0.10 mm/rev, 0.18 mm/rev and 0.28 mm/rev) under both traditional dry machining and chilled air dry machining condition by lathe machine with coated carbide cutting tool. The power consumption, surface finish and tool life is measured as the output of material’s machinability justification with the used of equipment such as power analyzer, surface profiler and optical video measurement system. The results showed that the better power efficiency had been obtained by the application of Vortex Tube which lowered the temperature by 11.17% in average; even it increased power consumption by 2.87% in average but decreased specific energy consumption by 22.11%. The performance of dry machining in tool life is better and 15.11% better in surface roughness compare to Vortex Tube. This happen due to the cooling effect of Vortex Tube that reduce machining temperature, lowered specific energy consumption but formed rapid harden strain on machined surface lead to higher value of surface roughness, while the surface material of coated carbide tool is easier to detached as the adhesive bond formed by removed chip and tool is stronger than the bond within base material of tool due to cooling effect which lead to tool wear easier. Recommendation of higher spindle speed and freed rate selection for this research had been proposed to observe the effectiveness of Vortex Tube on the performance of tool life and surface finish.